Empowerment unveiled: Gender dynamics and the impact of nutrition-sensitive agriculture interventions among ethnic minority groups in northern Vietnam - Nguyen Thi, Lan Thuy; van den Berg, Marrit; Stomph, TjeerdJan; Nabuuma, Deborah; Kramer, Berber (Elsevier BV, 2026)
Gender equality and women's empowerment are key global agendas, yet women often face marginalization compared to men. Nutrition-sensitive agriculture interventions (NSAs) often aim to benefit women but their impacts on women's empowerment remain unclear. This study focuses on: 1) assessing the empowerment levels of women and men from three ethnic minorities in rural northern Vietnam (Thai, H'Mong and Dao) with the Project-level women's empowerment in agriculture index (Pro-WEAI); 2) examining the potential of NSA to improve women's empowerment during COVID-19 pandemic; and 3) applying an intersectional lens by analyzing how empowerment and treatment effects vary by ethnic subgroups. We conducted a Randomized controlled trial (RCT) involving around 600 rural households from 36 clusters that were randomly assigned to one of the following three treatment arms: receiving agriculture and nutrition training; receiving seed provision on top of the training; and a control group. We found that both men and women experienced disempowerment, due to ethnicity and systemic ethnical marginalization. While no significant gender discrimination in resource access was found, women faced limited mobility, overburdened workload and diminished agencies. Empowerment experiences varied across ethnicities. The NSAs improved women's mobility and group membership, yet carried different implications across ethnicities, potentially due to the interaction between the intervention, initial contextual conditions and the COVID-19 pandemic. Nevertheless, NSAs alone cannot achieve structural empowerment. Meaningful and lasting empowerment requires integrated approaches that address interconnected social, political, and cultural factors.